Microbial characterization of a facultative residual sludge obtained from a biogas plant with ability to degrade commercial B10 diesel oil - Loureiro, Dana Belén (2020)
Fil: Loureiro, Dana Belén. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario. Grupo de Biotecnología de Materiales y Medioambiente; Argentina